Understanding the Role of Gibberellic Acid and Paclobutrazol in Terminal Heat Stress Tolerance in Wheat - Nagar, Shivani; Singh, V. P.; Arora, Ajay; Dhakar, Rajkumar; Singh, Neera; Singh, G. P.; Meena, Shashi; Kumar, Sudhir; Shiv Ramakrishnan, R. (Frontiers in Plant Science, 2021)
Understanding the physiological mechanism of tolerance under stress conditions is an imperative aspect of the crop improvement programme. The role of plant hormones is well-established in abiotic stress tolerance. However, the information on the role of gibberellic acid (GA) in abiotic stress tolerance in late sown wheat is still not thoroughly explored. Thus, we aimed to investigate the role of endogenous GA3 level in stress tolerance in contrasting wheat cultivars, viz., temperature-tolerant (HD 2643 and DBW 14) and susceptible (HD 2189 and HD 2833) cultivars under timely and late sown conditions. We created the variation in endogenous GA3 level by exogenous spray of GA3 and its biosynthesis inhibitor paclobutrazol (PBZ). Tolerant genotypes had higher antioxidant enzyme activity, membrane stability, and photosynthesis rate, lower lipid peroxidase activity, and better growth and yield traits under late sown conditions attributed to H2O2 content. Application of PBZ escalated antioxidant enzymes activity and photosynthesis rate, and reduced the lipid peroxidation and ion leakage in stress, leading to improved thermotolerance. GA3 had a non-significant effect on antioxidant enzyme activity, lipid peroxidation, and membrane stability. However, GA3 application increased the test weight in HD 2643 and HD 2833 under timely and late sown conditions. GA3 upregulated GA biosynthesis and degradation pathway genes, and PBZ downregulated kaurene oxidase and GA2ox gene expression. GA3 also upregulated the expression of the cell expansins gene under both timely and late sown conditions. Exogenous GA3 did not increase thermotolerance but positively affected test weight and cell expansins gene expression. No direct relationship existed between endogenous GA3 content and stress tolerance traits, indicating that PBZ could have conferred thermotolerance through an alternative mechanism instead of inhibiting GA3biosynthesis.